Livestock production development in AP Vojvodina - Trivunović, Snežana; Štrbac, Ljuba; Janković, Dobrila; Ivanović, Draško; Radović , Ivan; Mirkov, Mile; Pihler, Ivan; Bjedov, Siniša; Šaran, Momčilo (Acta Agraria Debreceniensis, 2018)
The aim of this paper is to present the effects of breeding program implementation on the development of animal breeding in Vojvodina since 2010. Data from the Main breeding organization (controlled population) and data from the Statistical Office of the Republic of Serbia (total population) were used as a basis for this research. The main breeding organization is the Departmant of Animal Science, Faculty of Agriculture, University of Novi Sad that implemented the main breeding programs in cattle, pig, sheep, goat, horse and poultry production. The milk yield in a recorded population of Holstein Friesian and Simmental cows shows evident phenotypic increasing trend as opposed to a population that is not controlled. The results of the selection measures in Vojvodina show that pig breeding has an upward trend and that we have an increasing number of small and medium (family) farms. Interest in sheep and goat production is increasing primarily because of the high demand for products made from sheep meat and goat milk and meat. In the recent decades, Vojvodina has been faced with a decrease in the number of horses. At the same time, there is an increasing interest in sports horses and recreation. According to poultry production results of parental flocks, an increasing tendency was observed in the production of controlled flocks recently, while the number of breeding stock breeders was reduced.